2009
DOI: 10.2174/138161209788453284
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells as Target in Cancer Therapy

Abstract: A close interaction of cancer cells with their microenvironment is important for their growth and survival. In this respect, the involvement of inflammatory cells in the initiation, promotion and progression of cancer has pointed to new therapeutic opportunities in the treatment of cancer. The main immune cell types implicated in tumor-associated inflammation are macrophages, dendritic cells, lymphocytes, neutrophils, eosinophils and mast cells. Their precise role in intercellular communication, regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…9 Mast cell presence in the tumor microenvironment guarantees the increased release of inflammatory and protumorigenic factors such as histamine, cytokines, and growth factors that all contribute to increasing tumorigenesis. 33 Here, we have found increased infiltration of mast cells and mast cell markers in human CCA, and in support of our findings a study has shown that the density of mast cells is substantially higher in intrahepatic CCA tissues than in nonmalignant and mast cells found surrounding portal tracts. 34 In pancreatic ductal adenocarcinoma nongranulated mast cell density is substantially higher than in the control group, suggesting that mast cells may promote pancreatic tumor growth, 35 and, in a study that used colorectal cancer, mast cell presence and mast cell marker expression, including c-Kit (all up-regulated), were determined to be potential diagnostic markers for the early detection of colorectal cancer.…”
Section: Discussionsupporting
confidence: 91%
“…9 Mast cell presence in the tumor microenvironment guarantees the increased release of inflammatory and protumorigenic factors such as histamine, cytokines, and growth factors that all contribute to increasing tumorigenesis. 33 Here, we have found increased infiltration of mast cells and mast cell markers in human CCA, and in support of our findings a study has shown that the density of mast cells is substantially higher in intrahepatic CCA tissues than in nonmalignant and mast cells found surrounding portal tracts. 34 In pancreatic ductal adenocarcinoma nongranulated mast cell density is substantially higher than in the control group, suggesting that mast cells may promote pancreatic tumor growth, 35 and, in a study that used colorectal cancer, mast cell presence and mast cell marker expression, including c-Kit (all up-regulated), were determined to be potential diagnostic markers for the early detection of colorectal cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Although extensive studies demonstrate a protumorigenic role for mast cells (reviewed in Ref. 16), antitumor actions of mast cells have also been reported. In vitro studies have demonstrated mast cells can mediate direct TNF-mediated tumor cell cytotoxicity (17,18).…”
mentioning
confidence: 99%
“…They support angiogenesis by expression of proangiogenic factors and by inhibition of ECM remodeling the MCs support tumor spread and metastasis. Tumor-associated mast cells are also regarded as potential therapeutic targets [124][125][126][127][128] and prognostic factor [129][130][131].…”
Section: Fibroblasts and Mast Cellsmentioning
confidence: 99%
“…Activated MC located in the TME release angiogenic and tumor growth stimulating factors [124,125,381]. Recent findings indicate that tumor-associated mast cells might represent valuable targets for therapeutic interventions, most notably to kinase inhibitors as c-Kit [128,382].…”
Section: Therapies Aimed At Cafs and Mast Cellsmentioning
confidence: 99%